Students’ feelings of isolation due to distance learning-during the crisis. A case study of Lebanon between COVID-19 and war - Kaawe, Elias; Stephan-Hayek, Christelle (Espacio Abierto, 2026)
This article explores the relationship between school isolation and the perception of the academic year among Lebanese students, by evaluating distance teaching modalities during two periods of crisis (the COVID-19 pandemic in 2020 and the September 2024 war in Lebanon). Data collected from 400 students reveals that in-person teaching remains widely preferred, but that isolation related to the war sometimes acted as a factor of resilience and success. These results highlight the need to integrate targeted psychosocial support into educational policies during times of crisis